2020
DOI: 10.1039/c9nr09011h
|View full text |Cite
|
Sign up to set email alerts
|

Use of lung-specific exosomes for miRNA-126 delivery in non-small cell lung cancer

Abstract: Engineered exosomes have become popular drug delivery carriers for cancer treatment. Systemic injection of organotropic exosome carrier leads to efficient targeting and efficacious anti-cancer outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 33 publications
6
101
0
Order By: Relevance
“…If we try to increase the coupling amount of Ale, it could be possible to get a better antiosteoporosis effect of Ale-EVs. It has been reported that MSC derived exosomes and microparticles could stimulate the repair and regeneration of tissues such as kidney, heart, and bone [29][30][31][32]. In this study, our results also showed that EVs from MMSCs could promote cell proliferation and trigger osteogenic differentiation of MMSCs in vitro (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…If we try to increase the coupling amount of Ale, it could be possible to get a better antiosteoporosis effect of Ale-EVs. It has been reported that MSC derived exosomes and microparticles could stimulate the repair and regeneration of tissues such as kidney, heart, and bone [29][30][31][32]. In this study, our results also showed that EVs from MMSCs could promote cell proliferation and trigger osteogenic differentiation of MMSCs in vitro (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…We can enrich MMSCsderived EVs with mRNAs or proteins that used to treat osteoporosis by genetic engineering technology [34][35][36], and strengthen the anti-osteoporosis effect of Ale-EVs. Besides, we also could load other drugs such as nucleic acid drugs [32,37], small molecule drugs [38] into the target-delivery system to achieve the purpose of combined treatment of osteoporosis…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MSC-derived exosomes and microparticles could stimulate the repair and regeneration of tissues such as kidney, heart, and bone. [33][34][35][36][37] Exosomes contain functional mRNAs, lncRNA, tRNA and miRNAs, as well as proteins. In addition, these contents play a positive role in osteogenic differentiation and proliferation.…”
mentioning
confidence: 99%
“…We can enrich mMSCs-derived EVs with mRNAs or proteins to treat osteoporosis by genetic engineering technology, [57][58][59] and strengthen the antiosteoporosis effect of Ale-EVs. Besides, we also could load other drugs such as nucleic acid drugs, 36,60 small molecule drugs 61 into the target-delivery system to achieve the purpose of combined treatment of osteoporosis.…”
mentioning
confidence: 99%
“…In addition, a recent study reported that exosome transportation was an important regulator in the formation and progression of lung cancer, and that the inhibition of exosomes could inhibit tumor proliferation. 32 In this study, microscopic observation showed that the fluorescently-labeled exosomes were able to enter the lung cancer cells. We separated and isolated G-MDSC-derived exosomes and found that exosomes promoted the proliferation of lung cancer in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 65%